2008
DOI: 10.1002/cphc.200800002
|View full text |Cite
|
Sign up to set email alerts
|

The Transition from pH Waves to Iodine Waves in the Iodate/Sulfite/Thiosulfate Reaction–Diffusion System

Abstract: Nonlinear spatial temporal behavior of the iodate/thiosulfate/sulfite reaction is investigated both in a stirred and spatially extended media. In accord with the temporal dynamics in the homogeneous media, both propagating fronts and target patterns are achieved in the spatially extended medium. On increasing the iodate concentration the system evolves from exhibiting propagating fronts to circular waves and then shows target patterns and finally the iodine waves. Influences of concentrations of sulfite, thios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…When the two fronts collide, there is no more possibility for oscillations, since thiourea does not consume protons any more. A seemingly similar phenomenon, separated iodine and pH fronts, is observed in the iodate−sulfite−thiosulfate reaction under batch conditions …”
Section: Discussionsupporting
confidence: 69%
“…When the two fronts collide, there is no more possibility for oscillations, since thiourea does not consume protons any more. A seemingly similar phenomenon, separated iodine and pH fronts, is observed in the iodate−sulfite−thiosulfate reaction under batch conditions …”
Section: Discussionsupporting
confidence: 69%
“…These systems are often called mixed Landolt reactions. As an example, the iodate–sulfite–thiosulfate (IST) reaction is autocatalytic with respect to hydrogen and iodide ions and shows complex pH oscillations, temperature oscillations in closed and/or CSTR system and presents pH- and iodine waves in a reaction–diffusion system . Skeleton mechanism of the reaction has been proposed and used to describe the phenomena mentioned above. , More recently, Liu et al found different spatiotemporal structures like iodine patterns, pH patterns, cellular fronts and Turing structures and proposed a mechanism with positive and negative feedback processes for explaining the pattern formation.…”
Section: Introductionmentioning
confidence: 99%
“…The skeleton mechanism of these combined systems has been accepted , and even a temperature oscillation could be explained in case of the iodate−sulfite−thiosulfate system . More recently, these systems are thoroughly studied to produce different spatiotemporal structures and may thus have potential applications in designing chemical waves, Turing structures, and even pH responsive gels with rhythmical motions. Therefore, to gain deeper insight into the intimate details of the Landolt reaction perturbed by thiosulfate we decided to investigate the later phase of thiosulfate−iodate reaction. Although the detailed kinetics and the mechanism of the thiosulfate−iodate reaction was already studied 80 years ago by Rieder, recent studies have pointed out ,, that the reaction cannot exclusively produce tetrathionate, sulfite has to be formed as well to explain adequately the batch pH oscillatory behavior.…”
Section: Introductionmentioning
confidence: 99%